Killing stalking. 3 - Koogi (Seven Seas Entertainment, 2023)
Things didn't end well for Min Jieun, and now Oh Sangwoo and Yoon Bum have a body on their hands. Can they dispose of it without getting caught? And what will Officer Yang Seungbae do when he finds out that Oh Sangwoo was the last person the missing girl was with?